RESEARCH ON THE PROFESSIONAL ORIENTATION OF HIGH SCHOOL STUDENTS DURING MARTIAL LAW IN UKRAINE - Lomakin, Gennadiy; Sapielnikova, Tetiana (Sworld-Us Conference proceedings, 2025)
The abstracts present the results of the study. The relationship between the individual and personal qualities of high school students and their professional self-determination has been revealed. Psychological factors that ensure the formation of professi